2017
DOI: 10.1186/s12891-017-1640-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-vascularised fibula grafts for reconstruction of segmental and hemicortical bone defects following meta- /diaphyseal tumour resection at the extremities

Abstract: BackgroundThe reconstruction of meta−/diaphyseal bone defects following bone tumour resection is challenging, and biological treatment options should be applied whenever possible, especially in benign lesions and early stage sarcomas. We aimed to evaluate the results of segmental (SR) and hemicortical reconstructions (HR) at the extremities using non-vascularised fibula grafts.MethodsWe retrospectively enrolled 36 patients who were treated with non-vascularised fibula reconstructions (15 SR, 21 HR) after bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 47 publications
2
44
0
2
Order By: Relevance
“…The Q-DASH score, by which functionality was assessed, was median 6.8 (2.28 to 29.50). Although satisfactory results were obtained in general (4,10,11), the patients stated that they had difficulty in washing their backs mostly. According to the LEFS score (mean 76.5±2.81) in which the lower extremity was used as a donor, all subjects regained their lower extremity functions almost completely at the end of the follow-up.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The Q-DASH score, by which functionality was assessed, was median 6.8 (2.28 to 29.50). Although satisfactory results were obtained in general (4,10,11), the patients stated that they had difficulty in washing their backs mostly. According to the LEFS score (mean 76.5±2.81) in which the lower extremity was used as a donor, all subjects regained their lower extremity functions almost completely at the end of the follow-up.…”
Section: Resultsmentioning
confidence: 98%
“…Lenze et al (10) reported a direct proportional relationship between union time and defect size. Furthermore, Lenze et al (10) also reported that the rate of mechanical complications was increased in NVFGs above 12 cm and Schuh et al (24) reported 10 cm. Thus, the use of vascularized grafts became more advantageous.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Lenze et al concluded that the procedure was a valuable procedure in defects less than 12 cm in length with an excellent union rate with minimum complications. 10 El-Sayed et al in a study of 12 patients with post traumatic bone defects, reported union in 11 cases (union rate of 92%) in an average period of 4 months. 11 They used plate and screws for upper limb defects and external fixators for tibia with cortico-cancellous bone graft along the entire length of fibular graft to augment graft uptake.…”
Section: Discussionmentioning
confidence: 97%